2016
DOI: 10.1155/2016/2810143
|View full text |Cite
|
Sign up to set email alerts
|

Mass Psychogenic Illness: Demography and Symptom Profile of an Episode

Abstract: Background. Mass psychogenic illness has been a recurrent phenomenon in Bangladesh over recent times. Objectives. This study was aimed at investigating the demographic characteristics and symptom profile of an outbreak of mass psychogenic illness occurring in a girls' high school. Methods and Materials. In 14 April 2013, a total of 93 students of a girls' high school suddenly developed various symptoms following intake of tiffin cake which resulted in panic and hospital admission. A descriptive, cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Other studies found an 18% prevalence of MFI in a study of MPI in an electronics plant ) and a higher prevalence of 56.8% of Mass Hysteria among adolescent female students in Taiwan (Chen et al, 2003;Colligan & Murphy, 1979 to the male workers. This result is consistent with the experimental study conducted by William (Lorber et al, 2007) and similar to other studies on the risk of MPI in the schools with the 90% female students (Olkinuora, 1984;Tarafder et al, 2016). The study presented that workers who ever worked in a factory had a higher risk of MFI compared to those working in a factory for the first time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies found an 18% prevalence of MFI in a study of MPI in an electronics plant ) and a higher prevalence of 56.8% of Mass Hysteria among adolescent female students in Taiwan (Chen et al, 2003;Colligan & Murphy, 1979 to the male workers. This result is consistent with the experimental study conducted by William (Lorber et al, 2007) and similar to other studies on the risk of MPI in the schools with the 90% female students (Olkinuora, 1984;Tarafder et al, 2016). The study presented that workers who ever worked in a factory had a higher risk of MFI compared to those working in a factory for the first time.…”
Section: Discussionsupporting
confidence: 91%
“…Mass Fainting Illness (MFI), previously known as Mass Psychogenic Illness (MPI) or Mass hysteria, has been found in many settings where large groups of people gather, such as schools, towns/villages, family groups, factories, institutions, and hospitals (Boss, 1997;Chowdhury & Brahma, 2005;Clements, 2003;Shakya, 2005). Psychological determinants can play a role in the risk of physical symptoms, and even fainting, excessive workload along with time pressure to a deadline and the subsequently threatening-induced layoff, from two or more people working closely within an intragroup and intergroup, but no organic disorders have been identified (Colligan & Murphy, 1979;Lee & Tsai, 2010;Tarafder et al, 2016). Researchers have found no congruence with determinant factors explaining this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, various studies published between 1973 and 1993 showed that schools are a very common place for mass psychogenic illness, accounting more than 50% of the events [ 8 , 29 ]. This was similarly evidenced from [ 30 , 31 ], South Africa [ 32 ], and Ethiopia [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 82%
“…The empirical evidence of mass hysteria, i.e., collective anxiety due to a perceived threat, dates back at least to the Middle Ages [ 30 , 31 ] and continues to numerous cases in modern times [ 32 , 33 , 34 , 35 ]. One of the most famous cases is a hysteria that developed after a radio play written by Orson Welles, War of the Worlds , was broadcasted in 1938.…”
Section: Literature History and Methodsmentioning
confidence: 99%